Counselling Working Class Women - McCarthy, Patricia R.; Reese, Robin G.; Schueneman, Jody M.; Reese, Jeffrey A. (Canadian Journal of Counselling and Psychotherapy, 2011)
The prevalence of psychological problems has been found to be highest for working class women (Lorion Bc Feiner, 1986), yet counsellors are often unprepared to counsel them effectively. This paper describes common characteristics and concerns of working class women clients, effective counselling approaches, and the difficulties and rewards for counsellors who deal with this population. Several research and training recommendations are presented.